2012
DOI: 10.2337/db12-0293
|View full text |Cite
|
Sign up to set email alerts
|

C-Peptide Prevents Hyperglycemia-Induced Endothelial Apoptosis Through Inhibition of Reactive Oxygen Species–Mediated Transglutaminase 2 Activation

Abstract: C-peptide is a bioactive peptide with a potentially protective role in diabetes complications; however, its molecular mechanism of protection against cardiovascular damage caused by hyperglycemia-induced apoptosis remains unclear. We investigated the protective mechanism of C-peptide against hyperglycemia-induced apoptosis using human umbilical vein endothelial cells and streptozotocin diabetic mice. High glucose (33 mmol/L) induced apoptotic cell death in endothelial cells via sequential elevation of intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
129
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 40 publications
8
129
0
Order By: Relevance
“…In this study we elucidated the essential role of TGase2 in VEGFinduced vascular leakage in the retinas of diabetic mice. Additionally, we recently reported that TGase2 is involved in diabetic vasculopathy resulting from apoptosis in endothelial cells and in the aorta, heart, and kidneys of diabetic mice (28). Another study using streptozotocin-induced diabetic rats demonstrated that TGase inhibition ameliorates the progression of diabetic nephropathy (33), suggesting the possible role of TGase2 in this disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study we elucidated the essential role of TGase2 in VEGFinduced vascular leakage in the retinas of diabetic mice. Additionally, we recently reported that TGase2 is involved in diabetic vasculopathy resulting from apoptosis in endothelial cells and in the aorta, heart, and kidneys of diabetic mice (28). Another study using streptozotocin-induced diabetic rats demonstrated that TGase inhibition ameliorates the progression of diabetic nephropathy (33), suggesting the possible role of TGase2 in this disease.…”
Section: Discussionmentioning
confidence: 97%
“…Transfection With Human TGase2-Specific siRNA HRECs were transfected with human TGase2-specific siRNA as described previously (28). Briefly, cells were transfected with various concentrations of human TGase2-siRNA or 100 nmol/L control siRNA (Dharmacon, Inc., Lafayette, CO) using siLentFect lipid reagent (Bio-Rad Laboratories, Hercules, CA) according to the manufacturer's instructions.…”
Section: Measurement Of In Situ Tgase Activitymentioning
confidence: 99%
“…C-peptide levels remained stable during the first years after islet transplantation, with some decline after year 6. Sustained positive C-peptide response itself may be of importance regarding diabetesassociated complications, given the increasing evidence of the positive effects of C-peptide regarding vascular, renal, and nerve dysfunction (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…However, hyperglycemia also directly impairs the cellular metabolism and causes abnormal changes of corneal epithelium, such as Akt-, epidermal growth factor receptor (EGFR)-, and Sirt1-mediated cell responses to environmental challenges (5)(6)(7). Moreover, excess oxidative stress, resulting from enhanced accumulation of reactive oxygen species (ROS) and impaired antioxidant capabilities in response to hyperglycemia, has been postulated as an important pathological mechanism, whereas the reduction of ROS attenuated the progression of various diabetes complications (8)(9)(10)(11)(12)(13), including in the cornea (5,14).…”
mentioning
confidence: 99%